Energy transfer in a hybrid system caused by the excitation of ultrashort plasmonic pulses - Lozano-Crisóstomo, N.; Sánchez-Mondragón, J. J.; May-Arrioja, D. A.; Agrawall, G. P. (Acta Universitaria, 2013)
In this paper we model and characterize the near infrared coupling between a plasmonic wire and a silicon nanowire. We also study the coupling parameters’ dependence on the dimensions of the directional coupler nanowires.